The effect of psychoeducation-based on transtheoretical model on depression in patients with coronary heart disease - Lindayani, Linlin; Yosep, Iyus; Purnama, Heni; Mutiar, Astri; Putri, Anisa Dwi (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Depression is the most common psychological condition among patients with coronary heart disease (CHD). Although psychoeducational programs (PEPs) based on the Transtheoretical Model (TTM) have shown promise for psychiatric patients, their application among individuals with medical conditions, particularly cardiovascular disease, remains limited—especially in Indonesia. Purpose: This study aimed to assess the effectiveness of a TTM-based PEP intervention in reducing depression among CHD patients. Methods: A quasi-experimental design was employed, involving 80 CHD patients hospitalized in the coronary care unit (CCU) of a private hospital in West Java, Indonesia, in 2022. Participants in the intervention group attended seven sessions, each lasting 60 to 90 minutes. Depression symptoms were measured using the Hamilton Depression Rating Scale (HDRS). An ANOVA was performed to compare pre- and post-intervention mean HDRS scores and subscale scores between the two groups. After accounting for attrition, the final analysis included data from 76 patients. Results: The participants had a mean age of 59.39 years (SD = 11.10) and a mean disease duration of 4.05 years (SD = 1.69). A paired t-test showed a significant reduction in the mean HDRS score of the intervention group, from 13.79 ± 2.84 pre-intervention to 10.16 ± 2.16 post-intervention (p < 0.0001). Most HDRS subscale scores also decreased significantly, except for insomnia, somatic/genital symptoms, and weight loss. ANCOVA confirmed significant differences between the two groups in overall HDRS scores. Conclusions: The findings suggest that TTM-based PEP is effective in reducing depression among CHD patients. Incorporating such programs alongside standard treatments is recommended for enhanced patient outcomes.